Interactive Effects of Rootstock and Training System on Photosynthesis, Biochemical Responses, and Yield in Vitis labrusca Under Subtropical Climate Conditions - Francisco José Domingues Neto; Marco Antonio Tecchio; Adilson Pimentel Junior; Harleson Sidney Almeida Monteiro; Mara Fernandes Moura-Furlan; José Luiz Hernandes; Elizabeth Orika Ono; Giuseppina Pace Pereira Lima; João Domingos Rodrigues (Horticulturae)
Climate change imposes significant challenges on viticulture, especially in subtropical regions, where thermal and water stresses impact vine physiology and yield. This study evaluated the effects of two rootstocks (‘IAC 766 Campinas’ and ‘106-8 Mgt’) and two training systems (low and high trellis) on the photosynthesis, biochemical parameters, and productivity of Vitis labrusca (‘Bordô’ and ‘Isabel’). The interaction between rootstock and training system significantly influenced gas exchange, chlorophyll fluorescence, antioxidant enzyme activity, and yield components. In ‘Bordô’, grapevines trained on high trellis and grafted onto ‘IAC 766 Campinas’ showed a 45.1% higher electron transport rate and 39.8% greater total chlorophyll content at flowering compared to the low trellis and ‘106-8 Mgt’ combination. Productivity increased by 49% under this combination. In ‘Isabel’, low trellis combined with ‘IAC 766 Campinas’ enhanced water use efficiency by 50% and SPAD index by 11%. These results highlight that selecting suitable rootstock and training system combinations can optimize physiological efficiency and yield, representing an effective adaptation strategy for viticulture under subtropical conditions.